PKM PENDAMPINGAN DAN PELATIHAN LARI 100 METER BERORIENTASI COMPETETITION PARTNER PADA ATLET NATIONAL PARALYMPIC COMITTE (NPC) INDONESIA - Nurhidayat Nurhidayat; Akhmad Azlan Khoirurrozikin; Eko Sudarmanto; Bima Febriyanto; Ahmad Fathoni; Haris Nugroho (Indonesian Collaboration Journal of Community Services, 2022)
The problem in Indonesia is that the practice of combining the results of the development of sports science and technology and the research results of sports academics in the training process of these athletes is still always encountering obstacles, because in addition to the centre for implementing sports science and technology it is not yet available and has not been integrated into athlete training programs, also because there is always a tendency resistance from practitioners in the field. Practitioners in the field still find it difficult to accept if the research results of academics are to be applied to the training process separately because they are often considered to interfere with the training process. Meanwhile, they are not very open and have the awareness to absorb information on the development of sports science and technology from scientific journals or other scientific forums, because they are too busy with tasks in the field. One of the sports is a physical condition and we jointly believe that there is a change in the improvement of athlete's achievement as a result of the action of applying science and technology in the training program in the sport concerned at the National Paralympic Committee of Indonesia. In addition, there is also a transfer of knowledge or changes in the behaviour of the trainer in the training process. This assistance is expected to produce a training model that can be implemented in the training process to improve the achievement of national superior sports that are oriented to the application of sports science and technology. The objectives of this PkM are: (i) To provide trainers with knowledge related to improving the 100-meter running oriented to competition partner, (ii) To provide assistance and training on the 100-meter running rules for Indonesian NPC athletes; (iii) to provide manuals related to competition partners for Indonesian NPC athletes. The objectives of this PkM are: (i) To provide trainers with knowledge related to improving the 100-meter running oriented to competition partner, (ii) To provide assistance and training on the 100-meter running rules for Indonesian NPC athletes; (iii) to provide manuals related to competition partners for Indonesian NPC athletes. The method implemented in this activity is based on the results of discussions between the proposer and partners. Furthermore, it was justified that the priority issues agreed to be resolved during the implementation of the PKM-PID program were to provide assistance and training related to increasing the 100-meter run oriented to the competition partner and to pay attention to the level of attractiveness, effectiveness, and efficiency of the training process developed/modified by the service team, so that Indonesian NPC athletes are interested in doing 100-meter running exercises oriented to competition partners. training model partner so that the problem of limited understanding of petanque can be solved together. What needs to be considered in this activity is how the renewal message can be delivered effectively and efficiently. For this reason, a communication process is needed, and the implementation of counselling is also carried out using the method of discussion/dialogue and interviews